Reproductive disorders in dairy cows of the southwest of Paraná - Giacomelli, Fernanda Elisa; PINTO NETO, ADALGIZA; MOTA, MARCELO FALCI; MARTINEZ, ANTÔNIO CAMPANHA; MERLINI, LUIZ SÉRGIO (Comunicata Scientiae, 2018)
Reproductive efficiency of dairy cows is evaluated directly considering the calving interval, which is affected by nutrition, irregular estrus cycle, prolonged anestrus, and reproductive diseases. Reproductive diseases cause economic losses due to diagnosis and treatment costs, and reduction in milk production. Thus, the objective of this study was to report the occurrence of the main reproductive disorders in dairy cows of the Southwest of Paraná, South of Brazil. Data of ultrasound diagnoses were collected from 2274 cows of 70 rural properties in the municipalities of Realeza, Planalto, Capanema, Pérola do Oeste, and Santa Isabel do Oeste from January 2014 to May 2015. Reproductive disorders were found in 24.50% (557/2274) of the animals evaluated; ovarian cysts (follicular, and luteal) were the most significant disorders, found in 16.13% (367/2274) of the cases. Other disorders were found less frequently. The occurrence of follicular and luteal cysts was observed especially in primiparous animals in months of pasture transition.